Effect of Varying Acetic Acid Concentration in the Total Phenolic and Flavonoid Content and Cytotoxicity of Ipomoea batatas Lam. (Convolvulaceae) Leaf Extracts - Ang, Aileen May Gabule; Jr, Arnold Lambu Agbu; Jumamil, Lorie Belle Puerto (Asian Journal of Biological and Life Sciences)
Introduction:Ipomoea batatas Lam. is grown in the Philippines for food. Its young leaves, reported to exhibit medicinal properties, are eaten fresh in salads with vinegar or shrimp paste.Objectives:However, the effect of varying acetic acid concentration on the extractability of its phenolics, flavonoid, and cytotoxic compounds using a safer and cheaper solvent such as acetic acid is not yet explored. Thus, the cytotoxicity and the total phenolics and flavonoid content of the aqueous acetic acid extracts ofI. batatasleaves is evaluated.Materials and Methods:Cytotoxicity of theI. batatasleaves extracted with 5%, 3%, and 1% aqueous acetic acid were determined through Brine Shrimp Lethality Assay (BSLA) while the total phenolics and flavonoid content were analyzed using Folin-ciocalteu and aluminium chloride method, respectively.Results and Discussion:The 5% aqueous acetic acid extract contains significantly higher amount of phenolics and flavonoids as compared to the 3% and 1%. BSLA also showed that the 5% aqueous acetic acid extract (LC50= 520.61 mg/L) exhibited cytotoxic activity while the 3% (LC50>1000 mg/L) and 1% (LC50>1000 mg/L) extracts were non-cytotoxic.Conclusion:The concentration of the acetic acid affects the extractability of the phenolics, flavonoids and cytotoxic compounds in theI. batatasleaves. The 5% aqueous acetic acid is more efficient in the extraction than the 3% and 1%. The use of acetic acid for the extraction of phenolics, flavonoids, and cytotoxic compounds fromI. batatasleaves can be a better option than other organic solvents.
Keywords: Acetic acid; cytotoxicity; Flavonoids; I. batatas; Phenolics.